Psychological distress and bowel cancer screening participation. Issue 2 (29th November 2022) - Anderson, Laura E.; Ireland, Michael J.; Myers, Larry; Avenell, Claire; Connaughton, Tanaya; Goodwin, Belinda C.
Abstract: Objective: To better understand barriers to participation in mail‐out bowel cancer screening programs, two survey studies tested the relationship between psychological distress and self‐reported bowel cancer screening. Methods: First, a nationally representative sample of Australians N  = 5421 completed measures of bowel cancer screening and psychological distress (using the Kessler Psychological Distress Scale; K10). Second, N  = 479 completed a survey measuring participation in the National Bowel Cancer Screening Program (NBCSP) and psychological distress using the Depression, Anxiety and Stress Scale. In both studies, logistic regressions were conducted to test relationships between psychological distress and self‐reported screening participation. Results: Study one found that psychological distress had a significant quadratic effect on having ever screened for bowel cancer, where screening rates were similar for those with low, moderate, or high levels of distress, but were lower for those with very high levels of distress. In study two, depression scores had a negative linear relationship with NBCSP participation (higher depression levels were associated with lower screening participation), and anxiety had a quadratic effect whereby NBCSP participation rates were higher with increasing levels of anxiety except in the severe category, where participation was significantly lower. Conclusions: Findings indicate that psychological distress has a complex relationship with screening, and those with extreme levels of distress consistently show lower participation rates. Special efforts to encourage screening may be required for those experiencing extreme psychological distress and mental health disorders.